The effects of different doses of curcumin compound on growth performance, antioxidant status, and gut health of broiler chickens challenged with Eimeria species - Yadav, Sudhir; Teng, Po-Yun; Souza dos Santos, Tatiane [UNESP]; Gould, Rebecca Lizabeth; Craig, Steven Wesley; Lorraine Fuller, Alberta; Pazdro, Robert; Kim, Woo Kyun (Elsevier, 2020)
Supplementation of broiler diets with feed additives such as chemotherapeutic drugs and antibiotics has side effects, meat residues, and antibiotics resistance complications. Plant-derived natural compounds could be safe and easy substitutes for chemical additives. One of the natural compounds is curcumin, the extract from herbal plant Curcuma longa, known for its antioxidant and antimicrobial properties which may be effective in reducing coccidia infection in poultry. The objective of this study was to evaluate the effects of curcumin on Eimeria challenged (C) and nonchallenged (NC) Cobb 500 broilers. A total of 360 12-day-old male chicks were housed in 36 cages in a completely randomized design with 6 replicates per treatment of 10 birds each cage. The six corn–soybean meal–based treatment diets were fed from day 12 to 20 to C and NC birds in 3-by-two factorial arrangement: nonchallenged control (NCC), NC + 100 mg/kg curcumin, NC + 200 mg/kg curcumin, challenged control (CC), C + 100 mg/kg curcumin, and C + 200 mg/kg curcumin. Broilers in C groups were inoculated orally with 50,000 oocysts of Eimeria maxima, 50,000 oocysts of Eimeria tenella, and 250,000 oocysts of Eimeria acervulina on day 14. The intestinal permeability (day 19), growth performance parameters, and intestinal lesion scoring were measured and recorded on day 20. The means were subjected to two-way ANOVA, and main factors effect and their interactions were considered. The growth performance and permeability were higher (P < 0.001) in the NC and C groups, respectively. However, no interaction was observed between curcumin dose and cocci challenge on both of these parameters. Results from lesion scores and oocyst shedding showed reduction (P < 0.050) in birds fed C + 200 mg/kg curcumin compared with those fed C + 100 mg/kg curcumin or CC. Curcumin treatment showed higher production of GSH (P = 0.002) and total glutathione (GSH+2GSSG) (P = 0.002) but lower GSH/GSSG ratio (P < 0.001) than the NCC group. Curcumin exhibited some positive responses on antioxidant capacity, lesion score, and oocyst shedding in the present study, suggesting that curcumin alone or a combination with other feed additives could be a dietary strategy to improve gut health in broilers.
Keywords: broiler; curcumin; Eimeria spp.; glutathione; intestinal health